Development of learning modules of basic electronics-based problem solving in Vocational Secondary School - Mustofa Abi Hamid; Didik Aribowo; D. Desmira (Jurnal Pendidikan Vokasi, 2017)
This research aims to: (1) developing a basic electronics learning modules based on problem solving, (2) knowing the response of students and teachers towards basic electronics learning module based on problem solving, (3) knowing the increase in student learning outcomes on subjects Basic electronics. This research method using Research and Development approach to model ADDIE (Analysis, Design, Development, Implementation, Evaluation). The subject of this research development are the first grade of Installation Technique of Electricity Power at SMK Negeri 2 Pandeglang as much as 118 students and 3 teachers on Basic electronics subject of SMK Negeri 2 Pandeglang. Furthermore, data collected by the questionnaire and test. Test validity and reliability for the question form is done with a technique Pearson Correlation coefficient obtained 0.88 and coefficient value of Cronbach's Alpha is 0.892. The results of this research are showed that: 1) the basic electronics learning modules based on problem solving that developed in its entirety was declared eligible for use, with the result average of validation of material categories include very decent, and the result average of validation of media categories include very decent too. The readability is included in category of very decent and in terms of learning to use the modules is included in the category of very decent. Using modules in the learning process are known there is increasing with the average value of the students learning outcomes of 68.53 rises to 80.24. T-test analysis results known tcalculate = 11.76 and ttable = 1.69 which means that the student learning outcomes has a significant improvement